3D mitral annulus echocardiography assessment in patients affected by degenerative mitral regurgitation who underwent mitral valve repair with flexible band. Issue 12 (26th October 2022) - Pingitore, Annachiara; Polizzi, Vincenzo; Cardillo, Ilaria; Lio, Antonio; Ranocchi, Federico; Pergolini, Amedeo; Musumeci, Francesco
Abstract: Background: Degenerative mitral valve (MV) regurgitation (DMR) shows significative mitral annulus (MA) alterations; mitral valve repair (MVR) seeks to restore annular geometry and function, and the current use of flexible band seams to respect most annular mobility reducing parietal stress. Parameters of MV geometry obtained by 3D transesophageal echocardiography (3D‐TTE) analysis are crucial for surgical planning and postoperative success. The aim of this study was to assess, by means of a dedicated software, the variations of MA geometry and function in patients affected by DMR compared to controls and after MVR with flexible band. Methods: We enrolled 32 patients (cases) with severe DMR who underwent MVR using flexible band; we compare this group with 20 controls. The TEE with 3D MV images acquisition was performed in both groups and then analyzed in postprocessing by using a dedicated software. Results: There were no anthropometrics differences between cases and controls, both presented normal left ventricular ejection fraction. DMR group showed a significant increase of annulus dimensional parameters ( p = .001) and alteration of nonplanarity comparing to controls ( p < .05). The annuloplasty with flexible band induces a considerable reduction of MV dimensions comparing to preoperative data and restores physiological mobility and nonplanarity. There were no statistical differences between postoperative DMR and controls data, except for nonplanarity parameters ( p .05), maybe influenced by hemodynamic settings. Conclusions: MVR with annuloplasty using flexible band appears able to reinstate a more physiological anatomic conformation of the MA, without compromising its dynamic properties.